(untitled) (International Journal of Engineering and Computer Science, 2016)
Solar water pumping systems are a modern but field proven means of pumping water in locations where access to grid power is not available, or where the grid is not reliable. These systems use photovoltaic (PV) cells to convert sunlight into electricity to power DC pumps which can be used to pump groundwater or surface water.This system provide the power at all time even at cloudy days.To increase the efficient irrigation in agriculture.This system to achieve dc supply to ac supply which can be used for pumping application. Dc-Dc Buck boost converter used in pumping system is to stabilize the voltage for induction motor. The buck boost converter is used to stepup and stepdown the input voltage. A solar photovoltaic water pumping system (SPWPS) consists of PV array, motor-pump set, associated electronics and an On/OFF switch.